Ameliorative effect of Hibiscus sabdariffa leaf flavonoid extract on the PSA/CEA/AKT/MMP-9 signaling pathway in benign prostatic hyperplasia-induced rats - Ajiboye, B.O.; Famusiwa, C.D.; Oghenemine, E.E.; Imoleyemi, A.D.; Akinlolu, O.S.; Fatoki, T.H.; Agbolade, A.O.; Ojelabi, A.O.; Ajuwon, O.R.; Oyinloye, B.E.; Iriti, M.; Okesola, M.A.; et al. (Springer Science and Business Media Deutschland GmbH, 2026)
Benign prostatic hypertrophy (BPH) is a prevalent condition affecting the prostate gland of elderly men. This study investigated the effects of H. sabdariffa leaf flavonoid extracts on BPH induction in rats. Thirty-six male Wistar rats were split into six groups: normal controls, BPH-induced rats (3 mg/kg testosterone), and rats treated with BPH-induced with flavonoid extract (300 mg/kg and 150 mg/kg) or a standard drug (1 mg/kg finasteride). After 28 days, biochemical, histological, and molecular parameters were assessed. The extract rich in flavonoids from H. sabdariffa markedly (p < 0.05) decreased the amount of MDA and enhanced the activities of antioxidant enzymes in rats administered with BPH. The extracts substantially attenuated inflammatory markers such as IL-6, IL-1β, and TNFα levels. Histological examination revealed improved prostate architecture in the treated groups in contrast to those in BPH-induced rats. Additionally, substantial (p < 0.05) downregulation of CEA, AKT, MMP9, and PSA in the extract-treated groups was observed. HPLC characterization identified prominent flavonoids, with quercetin being the most abundant bioactive compound. The outcome of this study proffers the therapeutic activities of H. sabdariffa flavonoid extract on BPH rat model.